Damage and collapse mode of existing post tensioned precast concrete bridge: The case of Petrulla viaduct. (1st May 2018) - Anania, Laura; Badalà, Antonio; D'Agata, Giuseppe
Highlights: The effects of the manufacturing lacks on the failure mode are presented. FE analysis of the local mechanism which induces collapse are discovered and discussed. Brittle collapse due to the corrosion of the tendons is presented. Crack pattern understanding in post tensioned beams is discussed. Abstract: This paper describes an investigation into the collapse mode of a single-span, segmental post-tensioned concrete bridge caused both by the effect of chloride induced corrosion in Prestressed Post Tensioned Bridge and by some initial faults during tendons design. Collapse was determined by the breakage of the tendons and the wires inside the tendons appear completely rusted. A numerical investigation was also carried out in order to determine the local mechanisms that led to the collapse of a segment of the Petrulla Viaduct in the south of Italy (Sicily) after a widespread beam damage was found. The main damage is the consequence of both an inadequate grout cementitious mortar filling, capable of introducing chemicals by which corrosion travelled along the tendons, and an inadequate distance among the ducts employed. The latter produces rotation of the wings around a point in the transversal section.